Mastocytosis: Fertility and Pregnancy Management in a Rare Disease - Ferrari, Jacqueline; Benvenuti, Pietro; Bono, Elisa; Fiorelli, Nicolas; Elena, Chiara (Frontiers in Oncology, 2022)
Mastocytosis is a rare disease, characterized by the presence, proliferation and accumulation of abnormal neoplastic MC in various organ systems, including skin, bone marrow, spleen and gastrointestinal tract. Clinical manifestations are highly heterogeneous, as they result from both MC mediator release and MC organ infiltration. Both pregnancy, a lifetime dominated by huge physiological changes, and labor can provide triggers that could induce worsening of mastocytosis symptoms. On the other hand, mastocytosis has relevant implications in obstetric management and prenatal care during all the pregnancy. In this review article, current knowledge about the impact of mastocytosis on fertility and pregnancy outcome will be reviewed and discussed, with the aim to provide clinical practice guidance for the evaluation and management of pregnancy and delivery in patients with cutaneous and systemic mastocytosis.